Central nervous system teratomas in infants: A report of two cases - Shatavisha DasGupta; Sanghamitra Mukherjee; Ram Narayan Das; Anway Sen; Uttara Chatterjee; Chhanda Datta; Sandip Chatterjee (Wolters Kluwer Medknow Publications, 2015)
Intracranial teratomas are uncommon neoplasms with most of them being encountered in the pediatric age group. Teratomas are composed of derivatives of all the three germ cell layers and are classified into mature, immature and teratoma with malignant transformation. Two cases of intracranial teratomas in infants are presented here with the idea of highlighting this relatively uncommon condition in an uncommon age.